Мониторинг коррозионного состояния железобетона и качества процесса катодной защиты посредством анализа переходной функции спада поляризационного потенциала - Панченко, В. А. (НТУ "ХПИ", 2010)
У роботі приведені результати експериментальних досліджень в діагностиці катодного захисту залізобетону. Запропоновані параметри і методи моніторингу. Публікація розкриває можливості простого аналізу функції спаду поляризаційного потенціалу для додаткової оцінки стану об'єкту і протікання процесу.

In the work the results of experimental researches in diagnostics of cathode protection of reinforced concrete are carried out. The parameters and methods of monitoring are offered. The publication opens opportunities of the simple analysis of function of recession of polarizing potential for an additional estimation of a condition of object and course of process.
Keywords: железобетонные конструкции; коррозия; электрохимическая защита железобетона; поляризационный потенциал; электрод сравнения